(untitled) (Communication & Society, 2019)
While a far from recent phenomenon, fake news has acquired a very special significance in the wake of the latest US elections. Against a broad background of different definitions and subtypes that require us to find a new, broader definition of the concept of fake news, the main debate about it concerns its scope and reach, which vary primarily in terms of intentionality and exactly how it disrupts the information process. With the discussion also focusing on the threats to (McChesney, 2014; Fisher, 2018) and opportunities for (Beckett, 2017) journalism itself, we seek to expand the debate on fake news to its impact on the dimension of trust in news. The starting point is Fletcher and Nielsen’s (2017) idea that, because they don’t make a clear distinction between real and fake news, Internet users feel a generalised sense of distrust in the media. Using data from the latest (2018) Reuters Digital News Report survey of a representative sample of the Portuguese Internet-using population, we describe the main reasons why the Portuguese (increasingly familiar with fake news and disinformation and their impacts) have been displaying higher levels of trust in news than counterparts in other countries, such as the United States –reasons that are linked to Portugal’s media system and historical context.